Place attachment mediates links between pro-environmental attitudes and behaviors among visitors to Mt. Bukhan National Park, South Korea - Yoon, Jee In; Lee, KangJae “Jerry”; Larson, Lincoln R. (Frontiers in Psychology, 2024)
Efforts to understand visitors' participation in pro-environmental behaviors (PEB) are important for protected area management. Previous research in nature-based recreation settings suggests environmental attitudes may affect PEB, and that these relationships might be mediated by different dimensions of place attachment (place identity and place dependence). We used structural equation modeling to test the mediating effect of hikers' place attachment in the relationship between environmental attitudes and PEBs that occur within (on-site) and outside a protected area (off-site): Mt. Bukhan National Park in South Korea. Results showed that cognitive (environmental knowledge) and affective (environmental sensitivity) components of environmental attitudes were significant predictors for place attachment. Place identity was linked to off-site PEB, while place dependence was a key antecedent for both off-site and on-site PEBs. Our findings could help researchers and practitioners better understand how place attachment forms and how it can impact outdoor recreationists' behavior, ultimately helping to promote PEBs and facilitate sustainable management goals.